Why Metacognition Is Not Always Helpful - Norman, Elisabeth (Frontiers in Psychology, 2020)
In many situations, actively engaging in metacognition may improve cognitive achievement and subjective wellbeing. However, the potential disadvantages of metacognitive engagement are only rarely communicated in metacognition research. In this paper I outline three ways in which metacognition may reduce cognitive achievement and psychological wellbeing. First, metacognition may sometimes actively interfere with task performance. Second, the costs of engaging in metacognitive strategies may under certain circumstances outweigh its benefits. Third, metacognitive judgments or feelings involving a negative self-evaluation may detract from psychological wellbeing. The main contribution of this paper is to integrate findings from different research traditions in order to illustrate the three suggested ways in which metacognition may be unhelpful. An implication of this overview is that although metacognition is most often beneficial to cognitive achievement and subjective wellbeing, one should bear in mind that it may also have the opposite effect. It is important for researchers and practitioners to take this potential downside of metacognition into account. Practitioners might find it useful to consider the following three questions that relate to my aforementioned claims: Is the nature of the task such that metacognition could interfere with performance? Is the cognitive demand required by the metacognitive strategy disproportionally large compared to its potential usefulness to cognitive achievement? Does metacognition lead to an unhelpful comparison of oneself to others? The same considerations should be kept in mind when researchers and practitioners communicate the potential implications of research findings in metacognition research to audiences within and beyond the research community.